Avaliação das perdas na colheita do algodão em diferentes velocidades da colhedora - Viotto, Gabriela de Faria Veiga (2015)
Losses during harvesting of agricultural products is common, and in the light of various problems, among them stands the forward speed of the harvester. Thus, the objective of this study was to detect losses in cotton harvesting depending on the harvester travel speed in the 2012/2013 and 2013/2014 seasons, trying to relate them to phenological factors directly related to the operation and that can contribute to improved crop quality. The evaluation of crop losses were held at the Farm Airport, located at Sinop-MT, with a harvester brand John Deere cotton, model 7760, with 257.43 kW (350 hp) of power in the engine, with 6 platform Harvesting unit lines, which uses the picker harvesting system. The varieties grown in the Farm Airport were FM951LL and FM975WS in the 2012/2013 harvest and 2013/2014, respectively, sown at a spacing of 0.73 and 0.76 meters. We used a simple random sampling method, with scheme tracks, in order to infer the population, about the variables studied. In each group were prepared compounds treatments two velocity of 1.14 and 1.36 ms-1 (4.1 and 4.9 km h-1 ). For each treatment were used three replications and 24 experimental units for each track and 48 in total. The tracks are 147.80 m long and 20.50 m wide each (3029.90 m²), the total area used in the experiment of 29,412.20 m² (2.94 ha-1 ) in each assessment. The data collected for the phenological characterization of culture in each property were analyzed using descriptive statistics to characterize the behavior and variability. The results of the losses were subjected to analysis of variance with test applications "F" and the means were compared by Tukey test at a significance level of 5% probability. We sought to evaluate before assagem the harvester, maximum productivity and the loss of pre-harvesting, collecting manually all the cotton sample area, and soon after the passage of the harvester proceeded to the collection of the total losses. It was observed that the loss of pre-harvest cotton averaged 32.49 and 2.17 kg ha-1 representing a percentage loss of 8.16 and 0.54% in crops 2012/2013 and 2013 / 2014 respectively, values considered relatively low and close to the values found in the literature for the state of Mato Grosso. The average total losses were found to be 534.32 and 210.86 kg ha-1 , representing a loss of 11.22 percent and 8.23% in the 2012/2013 and 2013/2014 seasons, respectively, these values remained close to the considered acceptable limit, which is 10% and the percentage losses.